Welding material for preparing copper-stainless steel gradient structure and CMT preparation method
By adopting a double-layer transition layer structure in the copper-stainless steel welding joint, the problem of poor formation and penetration cracking caused by the difference in thermal performance differences caused by the bronze-steel heterogeneous material welding connection. preparation.
Patent Information
- Application Number
- CN202411574132.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-06
AI Technical Summary
When welding and connecting copper-steel different materials, due to large differences in thermal physical properties, poor welding forming and steel side penetration and cracking are caused.
Use the copper-stainless steel gradient structure to prepare welding materials. By preparing the near steel side transition layer on the stainless steel matrix and the transition layer of the near-copper side on it to form a double-layer transition layer structure toughness.
The high-quality preparation of the copper-steel heterogeneous structure is realized, the problem of poor welding formation and the cracking of steel side penetration, and improved the strength and toughness of the welding joint.
Smart Images

Figure CN119328365A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal materials, and in particular relates to a welding material for preparing a copper-stainless steel gradient structure. The present invention also relates to a CMT preparation method for a copper-stainless steel gradient structure using the welding material for preparing a copper-stainless steel gradient structure. Background Art
[0002] Copper alloys have excellent electrical and thermal conductivity, and austenitic stainless steel has the characteristics of low cost and high strength. The copper-steel composite joint formed by combining the two has the advantages of both. However, the connection between copper and steel is a connection between dissimilar materials. Although no brittle phase is generated when the two are welded, the huge difference in their thermal physical properties leads to poor welding and easy formation of penetration cracks on the steel side. For the welding connection of dissimilar materials, preparing a transition layer is an effective solution. Summary of the invention
[0003] The purpose of the present invention is to provide a welding material for preparing a copper-stainless steel gradient structure, which is specifically used to solve the problems of poor forming and steel side penetration cracking caused by mismatched thermophysical properties when connecting copper-steel dissimilar structures.
[0004] Another object of the present invention is to provide a method for preparing a CMT of a copper-stainless steel gradient structure using a welding material for preparing a copper-stainless steel gradient structure.
[0005] The first technical solution adopted by the present invention is that the welding material for preparing the copper-stainless steel gradient structure includes a welding material for preparing a transition layer near the stainless steel side and a welding material for preparing a transition layer near the copper side; Among them, the welding material for preparing the transition layer near the stainless steel side includes powder and welding skin, wherein the powder includes the following components by mass percentage: the following components by mass percentage: Ni powder 40.0~50.0%, Cr powder 20.0~30.0%, Mo powder 5.0~8.0%, Nb powder 2.0~4.0%, Ag powder 2.0~4.0%, CeO2 powder 0.5~1.0%, and the rest is Fe powder; The welding material for preparing the transition layer near the copper side includes powder and solder skin, wherein the powder includes the following components by mass percentage: Ni powder 20.0-30.0%, Ag powder 10.0-20.0%, Mo powder 10.0-20.0%, Y2O3 powder 0.5-1.0%, and the rest is Cu powder.
[0006] The present invention is also characterized in that: The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 100 mesh to 200 mesh.
[0007] The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 20wt%~23wt%.
[0008] The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 30wt%~32wt%. The preparation method of welding materials for preparing the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 40.0-50.0% Ni powder, 20.0-30.0% Cr powder, 5.0-8.0% Mo powder, 2.0-4.0% Nb powder, 2.0-4.0% Ag powder, 0.5-1.0% CeO2 powder, and the rest Fe powder according to mass percentage; Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at a temperature of 200°C to 250°C for 1h to 3h to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2h to 6h; Step 3: Use alcohol to remove the grease on the surface of the steel strip, and wrap the powder prepared in step 2 in the 430 steel strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the powder filling rate of the welding material used for preparing the transition layer near the stainless steel side is controlled at 20wt%~23wt%; Step 4: After the first drawing process is completed, the die aperture is reduced in sequence, and finally a flux-cored welding wire with a diameter of 1.0-1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use; The preparation method of the welding material for preparing the transition layer near the copper side comprises the following specific steps: Step 1: Weigh 20.0-30.0% Ni powder, 10.0-20.0% Ag powder, 10.0-20.0% Mo powder, 0.5-1.0% Y2O3 powder, and the rest Cu powder according to mass percentage; Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at a temperature of 200°C to 220°C for 2h to 3h to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2h to 3h; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 30wt%~32wt%; Step 4: After the first drawing process is completed, the die aperture is reduced in sequence, and finally a flux-cored welding wire with a diameter of 1.0-1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0009] The second technical solution adopted by the present invention is to use the above-mentioned copper-stainless steel gradient structure preparation welding material to carry out the CMT preparation method of the copper-stainless steel gradient structure, and the specific steps are as follows: (1) First, select the welding material for preparing the transition layer near the stainless steel side to prepare the transition layer near the steel side on the surface of the stainless steel substrate. The CMT welding current is 180A~200A, the thickness of the cladding layer is 3mm~5mm, and the interlayer temperature is below 100℃ to ensure the dimensional accuracy of the cladding layer. (2) Next, select the welding material for preparing the transition layer near the copper side to prepare the transition layer near the copper side on the transition layer near the steel side. The CMT welding current is 200A~220A, the thickness of the cladding layer is 3mm~5mm, and the interlayer temperature is below 100℃ to ensure the dimensional accuracy of the cladding layer. (3) Finally, S201 welding wire was used to prepare the copper substrate by arc surfacing on the transition layer near the copper side. The CMT welding current was 220A~250A, the thickness of the surfacing layer was 10mm~15mm, and the surfacing was continuous without controlling the layer temperature.
[0010] The beneficial effects of the present invention are: (1) The present invention aims to solve the problems of poor welding forming and cracking on the steel side caused by the large difference in thermophysical properties during the welding connection of copper and stainless steel dissimilar materials, and proposes to use a double-layer transition layer to prepare a copper-steel gradient structure, thereby obtaining a high-quality copper-steel heterogeneous structure. The welding material of the present invention is specifically used to solve the problems of poor forming and penetration cracking on the steel side caused by the mismatch of thermophysical properties when connecting copper-steel dissimilar structures.
[0011] (2) The near-steel side transition layer prepared on the 410 stainless steel substrate of the present invention also adopts a stainless steel system, and the alloy system is Fe-Cr-Ni. The alloy system has little difference in alloy elements with the 410 stainless steel, and can ensure high-quality metallurgical bonding with the 410 stainless steel substrate.
[0012] (3) The transition layer near the copper side of the present invention adopts a copper-based welding material and adds elements such as Ni, Ag, and Mo. These elements are also added to the transition layer near the steel side. Therefore, adding these elements to the transition layer near the copper side ensures the excellent bonding strength of the transition layer on this side while also ensuring the metallurgical bonding performance with the transition layer on the stainless steel side.
[0013] (4) The present invention uses a CMT arc to prepare a near-steel layer transition layer on a 410 stainless steel substrate, and prepares a near-copper layer transition layer on the near-steel layer transition layer, ultimately forming a copper-steel gradient structure.
[0014] (5) In order to solve the problem of poor connection quality caused by the large difference in thermophysical properties when copper and steel are directly welded, the present invention proposes a strategy for preparing a gradient transition layer. The gradient transition layer can achieve a continuous transition of alloy elements from the copper side to the steel side, thereby reducing stress concentration in the joint and improving the strength and toughness of the joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Schematic diagram of the copper-stainless steel gradient structure prepared by CMT arc in the present invention; Figure 2 The microstructure of the transition layer near the steel layer in the copper-stainless steel gradient structure prepared in Example 2; Figure 3 The microstructure of the transition layer near the copper layer in the copper-stainless steel gradient structure prepared in Example 2; Figure 4 The tensile fracture morphology of the copper-stainless steel gradient structure prepared in Example 2 was observed by scanning electron microscopy. DETAILED DESCRIPTION
[0016] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0017] The present invention provides a welding material for preparing a copper-stainless steel gradient structure, including a welding material for preparing a transition layer near the stainless steel side and a welding material for preparing a transition layer near the copper side; Among them, the welding materials for preparing the transition layer near the stainless steel side include powder and welding skin, wherein the powder includes the following components by mass percentage: the following components by mass percentage: Ni powder 40.0~50.0%, Cr powder 20.0~30.0%, Mo powder 5.0~8.0%, Nb powder 2.0~4.0%, Ag powder 2.0~4.0%, CeO2 powder 0.5~1.0%, and the rest is Fe powder, and the sum of the mass percentages of the above components is 100%; The welding material for preparing the transition layer near the copper side includes powder and solder skin, wherein the powder includes the following components by mass percentage: Ni powder 20.0-30.0%, Ag powder 10.0-20.0%, Mo powder 10.0-20.0%, Y2O3 powder 0.5-1.0%, and the rest is Cu powder, and the sum of the mass percentages of the above components is 100%.
[0018] The purity of each raw material component powder is ≥99.9%.
[0019] The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 100 mesh to 200 mesh.
[0020] The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 20wt%~23wt%.
[0021] The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 30wt%~32wt%. The roles and functions of the main components of the above welding materials are as follows: (1) The main element of the welding material for preparing the transition layer near the stainless steel side is Fe (from 430 weld skin and flux): Since the first principle of the welding material for preparing the transition layer on the stainless steel side is to achieve a good metallurgical bond with the stainless steel substrate. In the present invention, 410 stainless steel is used as the substrate, and the Fe-Cr-Ni alloy system is designed. The main element in the welding material is also Fe, so that a good bonding strength with the stainless steel substrate can be ensured.
[0022] (2) The main added element of the welding material for the preparation of the transition layer near the stainless steel side is Cr (from 430 weld skin and flux): The addition of Cr is also for the good metallurgical bonding between the transition layer and the 410 stainless steel substrate, and the Cr content in the welding material for the transition layer near the stainless steel side is higher than that of the 410 stainless steel substrate, which can reduce the transition of the Fe element in the transition layer to the near-copper layer. According to the Cr-Fe binary phase diagram, the solid solubility of Cr in Fe is large, and the weldability of the two is good; according to the Cr-Cu binary phase diagram, although the solid solubility of Cr in Cu is low, the two will not form a brittle phase.
[0023] (3) The main added element of the welding material for preparing the transition layer near the stainless steel side is Ni (from the powder): According to the Fe-Ni and Cu-Ni binary phase diagrams, Ni is an element that can form metallurgical bonds with both Fe and Cu. Therefore, adding Ni to the transition layer near the stainless steel side can not only improve the bonding strength with the stainless steel matrix, but also ensure high-quality bonding with the copper side. In addition, Ni and Cr are mutually soluble in each other, so the addition of Ni can make up for the low solid solubility of Cr and Cu.
[0024] (4) Mo and Nb elements (from powder) are added to the welding material used to prepare the transition layer near the stainless steel side: Mo and Nb elements are solid solution strengthening elements for the Fe matrix. These two elements can be dissolved in the Fe matrix, causing lattice distortion, thereby improving the strength of the transition layer near the stainless steel side.
[0025] (5) Ag element (from powder) is added to the welding material used to prepare the transition layer near the stainless steel side: The main purpose of adding Ag element here is to lower the melting point of the welding material. From the binary phase diagrams of Ag-Fe and Ag-Cu, it can be seen that neither of them will generate brittle phases, so Ag is an element that can effectively lower the melting point of welding materials.
[0026] (6) CeO2 powder (from powder) is added to the welding material for preparing the transition layer near the stainless steel side: Since the transition layer near the steel side is designed to be a stainless steel system, and a ferritic stainless steel system, ferritic stainless steel often has coarse grains and weak grain boundary bonding. Therefore, adding CeO2 elements to the welding material for the transition layer near the steel side can effectively purify the ferrite grain boundary and reduce the grain size.
[0027] (7) The main element of the welding material used to prepare the transition layer near the copper side is Cu (from the copper strip solder skin and flux): the copper side transition layer is directly connected to copper, so the design with Cu as the main element can ensure excellent metallurgical bonding performance.
[0028] (8) The main added element of the welding material for preparing the transition layer near the copper side is Ni (from the powder): This element is added to both the transition layer near the steel side and the transition layer near the copper side. On the one hand, it is to achieve an excellent combination of the two transition layers, and on the other hand, it is to achieve the connection between the transition layer near the copper side and the copper matrix, because Cu-Ni is an alloy system with infinite solid solution. The solid solution of Ni in Cu will also increase the strength of the transition layer on the copper side.
[0029] (9) Ag element (from powder) is added to the welding material used to prepare the transition layer near the copper side: According to the Cu-Ag binary phase diagram, the solid solution between the two is large and the weldability is excellent. Ag element is also added to the transition layer near the steel side. When added to the transition layer near the copper side, it can achieve a good metallurgical bond between the two transition layers. And the addition of Ag can also reduce the melting point of the copper-based welding material, thereby reducing the penetration cracks on the steel side.
[0030] (10) Mo (from powder) is added to the welding material used to prepare the transition layer near the copper side: Mo is added to both the transition layer near the steel side and the transition layer near the copper side, which can improve the connection strength of the two transition layers. In addition, the solid solubility of Mo in the Cu matrix is relatively larger than that of Cr, so the addition of Mo can further improve the strength of the transition layer on the copper side.
[0031] (11) Y2O3 powder (from flux powder) is added to the welding material used to prepare the transition layer near the copper side: The transition layer near the copper side is mainly composed of Cu elements and has coarse grains, similar to the transition layer near the steel side. Therefore, rare earth oxides are added to refine the grain size of the transition layer near the copper side. Y2O3 oxide is added here, which is a rare earth oxide like CeO2 oxide in the transition layer near the steel side, but of different types. The main reason for choosing different rare earth oxides is to use the synergistic effect of different rare earth oxides to refine the grain size and purify the grain boundaries. The combined effect of multiple rare earth oxides is often more obvious than that of a single rare earth oxide.
[0032] The preparation method of welding materials for preparing the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 40.0-50.0% Ni powder, 20.0-30.0% Cr powder, 5.0-8.0% Mo powder, 2.0-4.0% Nb powder, 2.0-4.0% Ag powder, 0.5-1.0% CeO2 powder, and the rest Fe powder, respectively, by mass percentage, and the sum of the mass percentages of the above components is 100%; Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at a temperature of 200°C to 250°C for 1h to 3h to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2h to 6h; Step 3: Use alcohol to remove the grease on the surface of the steel strip, and wrap the powder prepared in step 2 in the 430 steel strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the powder filling rate of the welding material used for preparing the transition layer near the stainless steel side is controlled at 20wt%~23wt%; Step 4: After the first drawing process is completed, the die aperture is reduced in sequence, and finally a flux-cored welding wire with a diameter of 1.0-1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use; The preparation method of the welding material for preparing the transition layer near the copper side comprises the following specific steps: Step 1: Weigh 20.0-30.0% Ni powder, 10.0-20.0% Ag powder, 10.0-20.0% Mo powder, 0.5-1.0% Y2O3 powder, and the rest is Cu powder, and the sum of the mass percentages of the above components is 100%; Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at a temperature of 200°C to 220°C for 2h to 3h to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2h to 3h; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 30wt%~32wt%; Step 4: After the first drawing process is completed, the die aperture is reduced in sequence, and finally a flux-cored welding wire with a diameter of 1.0-1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0033] The present invention also discloses a method for preparing a CMT of a copper-stainless steel gradient structure using the above-mentioned copper-stainless steel gradient structure preparation welding material, wherein the copper-stainless steel gradient structure preparation welding material comprises a welding material for preparing a transition layer near the stainless steel side and a welding material for preparing a transition layer near the copper side, such as Figure 1 As shown, the specific steps are as follows: (1) First, the welding material for preparing the transition layer near the stainless steel side is selected to prepare the transition layer near the steel side on the surface of the 410 stainless steel substrate, the CMT welding current is 180A~200A, the thickness of the cladding layer is 3mm~5mm, and the interlayer temperature is below 100°C to ensure the dimensional accuracy of the cladding layer; (2) Next, the copper-side transition layer preparation welding material is selected to prepare the copper-side transition layer on the steel-side transition layer, the CMT welding current is 200A-220A, the thickness of the cladding layer is 3mm-5mm, and the interlayer temperature is below 100°C to ensure the dimensional accuracy of the cladding layer; (3) Finally, S201 welding wire was used to prepare the copper substrate by arc surfacing on the transition layer near the copper side. The CMT welding current was 220A~250A, the thickness of the surfacing layer was 10mm~15mm, and the surfacing was continuous without controlling the layer temperature.
[0034] Example 1 The preparation method of the welding material for the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 40.0% Ni powder, 20.0% Cr powder, 5.0% Mo powder, 2.0% Nb powder, 2.0% Ag powder, 0.5% CeO2 powder, and the rest Fe powder according to mass percentage. The sum of the mass percentages of the above components is 100%.
[0035] Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 200°C for 1 hour to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 2 hours; Step 3: Use alcohol to remove grease from the surface of the steel strip, and wrap the powder prepared in step 2 in the 430 steel strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0036] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0037] The preparation method of the copper-side welding material comprises the following specific steps: Step 1: Weigh 20.0% Ni powder, 10.0% Ag powder, 10.0% Mo powder, 0.5% Y2O3 powder and the rest Cu powder respectively by mass percentage, and the sum of the mass percentages of the above components is 100%.
[0038] Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at 200°C for 2 hours to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2 hours; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0039] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0040] The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 100 meshes.
[0041] The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 20wt%.
[0042] The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 30wt%. The transition layer welding material prepared in Example 1 is used to prepare a copper-stainless steel gradient structure. The specific steps of the CMT preparation method are as follows (eg Figure 1 shown): (1) First, the stainless steel side welding material of the present invention is selected to prepare the steel side transition layer on the surface of the 410 stainless steel substrate, the CMT welding current is 180-200A, the thickness of the cladding layer is 3mm, and the interlayer temperature is 90°C to ensure the dimensional accuracy of the cladding layer; (2) Next, the copper-side welding material of the present invention is selected to prepare the copper-side transition layer on the steel-side transition layer. The CMT welding current is 200-220A, the thickness of the cladding layer is 3mm, and the interlayer temperature is 90°C to ensure the dimensional accuracy of the cladding layer. (3) Finally, S201 welding wire was used to prepare the copper substrate by arc surfacing on the above-mentioned transition layer near the copper side. The CMT welding current was 220~250A, the thickness of the surfacing layer was 10mm, and the surfacing was continuous without controlling the layer temperature.
[0043] After testing, the results of the copper-stainless steel gradient structure are as follows: (1) The transition layer near the stainless steel side is mainly ferrite, with no cracks or inclusion defects; (2) The transition layer near the copper side is mainly composed of Cu solid solution, with no cracks or inclusion defects. (3) The tensile strength of the copper-stainless steel gradient structure is 351 MPa, and the fracture position is on the copper side matrix.
[0044] Example 2 The preparation method of the welding material for the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 50.0% Ni powder, 30.0% Cr powder, 8.0% Mo powder, 4.0% Nb powder, 4.0% Ag powder, 1.0% CeO2 powder, and the rest Fe powder according to mass percentage. The sum of the mass percentages of the above components is 100%.
[0045] Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at a temperature of 250°C for 3 hours to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 6 hours; Step 3: Use alcohol to remove grease from the surface of the steel strip, and wrap the powder prepared in step 2 in the 430 steel strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.0 mm is obtained.
[0046] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0047] The preparation method of the copper-side welding material comprises the following specific steps: Step 1: Weigh 30.0% Ni powder, 20.0% Ag powder, 20.0% Mo powder, 1.0% Y2O3 powder, and the rest Cu powder according to mass percentage. The sum of the mass percentages of the above components is 100%.
[0048] Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at 220°C for 3 hours to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 3 hours; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.0 mm is obtained.
[0049] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0050] The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 200 meshes.
[0051] The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 23wt%.
[0052] The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 32wt%. The transition layer welding material prepared in Example 2 is used to prepare a copper-stainless steel gradient structure. The specific steps of the CMT preparation method are as follows ( Figure 1 shown): (1) First, the stainless steel side welding material of the present invention is selected to prepare the steel side transition layer on the surface of the 410 stainless steel substrate, the CMT welding current is 180-200A, the thickness of the cladding layer is 5mm, and the interlayer temperature is 80°C to ensure the dimensional accuracy of the cladding layer; (2) Next, the copper-side welding material of the present invention is selected to prepare the copper-side transition layer on the steel-side transition layer. The CMT welding current is 200-220A, the thickness of the cladding layer is 5mm, and the interlayer temperature is 80°C to ensure the dimensional accuracy of the cladding layer. (3) Finally, S201 welding wire was used to prepare the copper substrate by arc cladding on the above-mentioned transition layer near the copper side. The CMT welding current was 220~250A, the thickness of the cladding layer was 15mm, and the cladding was continuous without controlling the layer temperature.
[0053] After testing, the results of the copper-stainless steel gradient structure are as follows: (1) The transition layer near the stainless steel side is mainly ferrite, with no cracks or inclusion defects; (2) The transition layer near the copper side is mainly composed of Cu solid solution, with no cracks or inclusion defects. (3) The tensile strength of the copper-stainless steel gradient structure is 359 MPa, and the fracture position is on the copper side matrix.
[0054] Figure 2 The microstructure of the transition layer near the steel layer in the copper-stainless steel gradient structure prepared in Example 2. Figure 2 It can be seen that the transition layer near the steel side is mainly composed of single-phase ferrite with clear grain boundaries.
[0055] Figure 3 The microstructure of the transition layer near the copper layer in the copper-stainless steel gradient structure prepared in Example 2. Figure 3 It can be seen that the transition layer near the copper side is mainly composed of single-phase Cu structure with clear grain boundaries.
[0056] Figure 4 The tensile fracture surface of the copper-stainless steel gradient structure prepared in Example 2 was observed by scanning electron microscopy. Figure 4 It can be seen that the fracture surface is mainly dimple morphology, and the toughness is good.
[0057] Example 3 The preparation method of the welding material for the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 45.0% Ni powder, 25.0% Cr powder, 7.0% Mo powder, 3.0% Nb powder, 3.0% Ag powder, 0.7% CeO2 powder, and the rest Fe powder according to mass percentage. The sum of the mass percentages of the above components is 100%.
[0058] Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at 230°C for 2 hours to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 4 hours; Step 3: Use alcohol to remove grease from the surface of the steel strip, and wrap the powder prepared in step 2 in the 430 steel strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0059] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0060] The preparation method of the copper-side welding material comprises the following specific steps: Step 1: Weigh 25.0% Ni powder, 15.0% Ag powder, 15.0% Mo powder, 0.7% Y2O3 powder and the rest Cu powder respectively by mass percentage, and the sum of the mass percentages of the above components is 100%.
[0061] Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at 210°C for 2.5 hours to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2.5 hours; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0062] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0063] The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 100 meshes.
[0064] The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 21wt%.
[0065] The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 31wt%. The transition layer welding material prepared in Example 3 was used to prepare a copper-stainless steel gradient structure. The specific steps of the CMT preparation method are as follows ( Figure 1 shown): (1) First, the stainless steel side welding material of the present invention is selected to prepare the steel side transition layer on the surface of the 410 stainless steel substrate, the CMT welding current is 180-200A, the thickness of the cladding layer is 4mm, and the interlayer temperature is 70°C to ensure the dimensional accuracy of the cladding layer; (2) Next, the copper-side welding material of the present invention is selected to prepare the copper-side transition layer on the steel-side transition layer. The CMT welding current is 200-220A, the thickness of the cladding layer is 4mm, and the interlayer temperature is 70°C to ensure the dimensional accuracy of the cladding layer. (3) Finally, S201 welding wire was used to prepare the copper substrate by arc cladding on the above-mentioned transition layer near the copper side. The CMT welding current was 220~250A, the thickness of the cladding layer was 13mm, and the cladding was continuous without controlling the layer temperature.
[0066] After testing, the results of the copper-steel gradient structure are as follows: (1) The transition layer near the stainless steel side is mainly ferrite, with no cracks or inclusion defects; (2) The transition layer near the copper side is mainly composed of Cu solid solution, with no cracks or inclusion defects. (3) The tensile strength of the copper-steel gradient structure is 351 MPa, and the fracture position is on the copper side matrix.
[0067] Example 4 The preparation method of the welding material for the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 43.0% Ni powder, 23.0% Cr powder, 6.0% Mo powder, 3.5% Nb powder, 3.5% Ag powder, 0.9% CeO2 powder, and the rest Fe powder according to mass percentage. The sum of the mass percentages of the above components is 100%.
[0068] Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at 220°C for 1.3 hours to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2.6 hours; Step 3: Use alcohol to remove grease from the surface of the steel strip, and wrap the powder prepared in step 2 in the 430 steel strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.0 mm is obtained.
[0069] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0070] The preparation method of the copper-side welding material comprises the following specific steps: Step 1: Weigh 22.0% Ni powder, 12.0% Ag powder, 12.0% Mo powder, 0.6% Y2O3 powder and the rest Cu powder respectively by mass percentage, and the sum of the mass percentages of the above components is 100%.
[0071] Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 215°C for 2.3 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 2.3 hours; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.0 mm is obtained.
[0072] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0073] The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 200 meshes.
[0074] The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 23wt%.
[0075] The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 32wt%. The transition layer welding material prepared in Example 4 is used to prepare a copper-stainless steel gradient structure. The specific steps of the CMT preparation method are as follows (eg Figure 1 shown): (1) First, the stainless steel side welding material of the present invention is selected to prepare the steel side transition layer on the surface of the 410 stainless steel substrate, the CMT welding current is 180-200A, the thickness of the cladding layer is 3.5mm, and the interlayer temperature is 60°C to ensure the dimensional accuracy of the cladding layer; (2) Next, the copper-side welding material of the present invention is selected to prepare the copper-side transition layer on the steel-side transition layer. The CMT welding current is 200-220A, the thickness of the cladding layer is 3.5mm, and the interlayer temperature is below 60°C to ensure the dimensional accuracy of the cladding layer. (3) Finally, S201 welding wire was used to prepare the copper substrate by arc surfacing on the above-mentioned transition layer near the copper side. The CMT welding current was 220~250A, the thickness of the surfacing layer was 12.5mm, and the surfacing was continuous without controlling the layer temperature.
[0076] After testing, the results of the copper-stainless steel gradient structure are as follows: (1) The transition layer near the stainless steel side is mainly ferrite, with no cracks or inclusion defects; (2) The transition layer near the copper side is mainly composed of Cu solid solution, with no cracks or inclusion defects. (3) The tensile strength of the copper-stainless steel gradient structure is 347 MPa, and the fracture position is on the copper side matrix.
[0077] Example 5 The preparation method of the welding material for the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 49.0% Ni powder, 29.0% Cr powder, 5.50% Mo powder, 2.7% Nb powder, 2.8% Ag powder, 0.55% CeO2 powder, and the rest Fe powder according to mass percentage. The sum of the mass percentages of the above components is 100%.
[0078] Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 218°C for 2.8 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 5.7 hours; Step 3: Use alcohol to remove grease from the surface of the steel strip, and wrap the powder prepared in step 2 in the 430 steel strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0079] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0080] The preparation method of the copper-side welding material comprises the following specific steps: Step 1: Weigh 28.0% Ni powder, 19.0% Ag powder, 17.0% Mo powder, 0.58% Y2O3 powder and the rest Cu powder respectively by mass percentage, and the sum of the mass percentages of the above components is 100%.
[0081] Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 219° C. for 2.7 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 2.8 hours; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.
[0082] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
[0083] The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 100 meshes.
[0084] The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 22wt%.
[0085] The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 32wt%. The transition layer welding material prepared in Example 5 is used to prepare a copper-stainless steel gradient structure. The specific steps of the CMT preparation method are as follows (eg Figure 1 shown): (1) First, the stainless steel side welding material of the present invention is selected to prepare the steel side transition layer on the surface of the 410 stainless steel substrate, the CMT welding current is 180-200A, the thickness of the cladding layer is 3.2mm, and the interlayer temperature is 50°C to ensure the dimensional accuracy of the cladding layer; (2) Next, the copper-side welding material of the present invention is selected to prepare the copper-side transition layer on the steel-side transition layer. The CMT welding current is 200-220A, the thickness of the cladding layer is 3.9mm, and the interlayer temperature is 50°C to ensure the dimensional accuracy of the cladding layer. (3) Finally, S201 welding wire was used to prepare the copper substrate by arc surfacing on the above-mentioned transition layer near the copper side. The CMT welding current was 220~250A, the thickness of the surfacing layer was 11mm, and the surfacing was continuous without controlling the layer temperature.
[0086] After testing, the results of the copper-stainless steel gradient structure are as follows: (1) The transition layer near the stainless steel side is mainly ferrite, with no cracks or inclusion defects; (2) The transition layer near the copper side is mainly composed of Cu solid solution, with no cracks or inclusion defects. (3) The tensile strength of the copper-stainless steel gradient structure is 350 MPa, and the fracture position is on the copper side matrix.
Claims
1. A welding material for preparing a copper-stainless steel gradient structure, characterized in that: Including welding materials for preparing transition layer near stainless steel side and welding materials for preparing transition layer near copper side; Among them, the welding material for preparing the transition layer near the stainless steel side includes powder and welding skin, wherein the powder includes the following components by mass percentage: the following components by mass percentage: Ni powder 40.0~50.0%, Cr powder 20.0~30.0%, Mo powder 5.0~8.0%, Nb powder 2.0~4.0%, Ag powder 2.0~4.0%, CeO2 powder 0.5~1.0%, and the rest is Fe powder; The welding material for preparing the transition layer near the copper side includes powder and solder skin, wherein the powder includes the following components by mass percentage: Ni powder 20.0-30.0%, Ag powder 10.0-20.0%, Mo powder 10.0-20.0%, Y2O3 powder 0.5-1.0%, and the rest is Cu powder, and the sum of the mass percentages of the above components is 100%.
2. The welding material for preparing a copper-stainless steel gradient structure according to claim 1, characterized in that: The particle size of the powder used in the welding material for preparing the transition layer near the stainless steel side and the welding material for preparing the transition layer near the copper side are both 100 mesh to 200 mesh.
3. The welding material for preparing a copper-stainless steel gradient structure according to claim 1, characterized in that: The weld skin of the welding material for preparing the transition layer near the stainless steel side is 430 steel strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the stainless steel side is controlled at 20wt%~23wt%.
4. The welding material for preparing a copper-stainless steel gradient structure according to claim 1, characterized in that: The solder coating of the welding material for preparing the transition layer near the copper side is a copper strip with a thickness of 0.4 mm and a width of 7 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 30wt%~32wt%.
5. The welding material for preparing a copper-stainless steel gradient structure according to claim 1, characterized in that: The method for preparing the welding material for preparing the transition layer near the stainless steel side comprises the following specific steps: Step 1: Weigh 40.0-50.0% Ni powder, 20.0-30.0% Cr powder, 5.0-8.0% Mo powder, 2.0-4.0% Nb powder, 2.0-4.0% Ag powder, 0.5-1.0% CeO2 powder, and the rest Fe powder according to mass percentage; Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at a temperature of 200°C to 250°C for 1h to 3h to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2h to 6h; Step 3: Wrap the powder prepared in step 2 in a 430 steel strip through a flux-cored wire drawing device, and the aperture of the first drawing die is 2.6 mm; the powder filling rate of the welding material used for preparing the transition layer near the stainless steel side is controlled at 20wt%~23wt%; Step 4: After the first drawing process is completed, the die aperture is reduced in sequence, and finally a flux-cored welding wire with a diameter of 1.0-1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use; The method for preparing the welding material for preparing the transition layer near the copper side comprises the following specific steps: Step 1: Weigh 20.0-30.0% Ni powder, 10.0-20.0% Ag powder, 10.0-20.0% Mo powder, 0.5-1.0% Y2O3 powder, and the rest Cu powder according to mass percentage; Step 2: Place the powder weighed in step 1 in a vacuum heating furnace and heat it at a temperature of 200°C to 220°C for 2h to 3h to remove the crystal water in the powder; place the dried powder in a powder mixer and mix it thoroughly for 2h to 3h; Step 3: Use alcohol to remove grease from the surface of the copper strip, and wrap the powder prepared in step 2 in the copper strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; the powder filling rate of the welding material for preparing the transition layer near the copper side is controlled at 30wt%~32wt%; Step 4: After the first drawing process is completed, the die aperture is reduced in sequence, and finally a flux-cored welding wire with a diameter of 1.0-1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.
6. A method for preparing a CMT of a copper-stainless steel gradient structure using the welding material for preparing a copper-stainless steel gradient structure according to claim 1, characterized in that: The specific steps are as follows: (1) First, the welding material for preparing the transition layer near the stainless steel side is selected to prepare the transition layer near the steel side on the surface of the stainless steel substrate, the CMT welding current is 180A~200A, the thickness of the cladding layer is 3mm~5mm, and the interlayer temperature is below 100°C; (2) Next, the copper-side transition layer preparation welding material is selected to prepare the copper-side transition layer on the steel-side transition layer, the CMT welding current is 200A-220A, the thickness of the cladding layer is 3mm-5mm, and the interlayer temperature is below 100°C; (3) Finally, S201 welding wire was used to prepare the copper substrate by arc surfacing on the transition layer near the copper side. The CMT welding current was 220A~250A, the thickness of the surfacing layer was 10mm~15mm, and the surfacing was continuous without controlling the layer temperature.
Citation Information
Patent Citations
Laser welding method for T2 red copper and 301 stainless steel dissimilar materials
CN112775550A
Welding wire for large-thickness copper-steel butt welding, preparation method and welding method
CN117444466A
Build-up welding method for copper or copper-based alloy
JP2001047234A
Welding wire for dissimilar welding of cu and steel and preparation method thereof and method for welding cu and steel
US20220118543A1
Special flux-cored welding wire for deep-sea wet FCAW and preparation method therefor
WO2023160718A1